Effects of combined heat transfer on the thermo-economic performance of irreversible solar-driven heat engines - Ust, Yasin (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
A thermo-economic performance analysis and optimization has been carried out for an irrversible solar-driven heat engine with losses due to heat transfer across finite temperature differences, heat leak and internal irreversibilities. In the considered heat engine model, heat transfer from the hot reservoir is assumed to be simultaneous radiation and convection mode and the heat transfer to the cold reservoir is assumed to be convection mode. The effects of the technical and economical parameters on the thermo-economic performance have been investigated in order to see the collective effects of the radiation and convection modes of heat transfer. Also the optimal performance parameters of the heat engine, such as the thermal efficiency, temperatures of the working fluid and the ratio of heat transfer areas have been discussed in detail. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: irreversible; optimization; thermo-economic performance; solar-driven heat engine; ENTROPY GENERATION MINIMIZATION; OPTIMUM OPERATING-CONDITIONS; MAXIMUM POWER; THERMODYNAMIC OPTIMIZATION; REFRIGERATORS; EFFICIENCY; DESIGN; Science & Technology - Other Topics; Energy & Fuels